2013
DOI: 10.1186/1471-2458-13-335
|View full text |Cite
|
Sign up to set email alerts
|

Contraband tobacco on post-secondary campuses in Ontario, Canada: analysis of discarded cigarette butts

Abstract: BackgroundNo studies to date have assessed young adults’ use of First Nations/Native tobacco, a common form of contraband tobacco in Canada. This study examined the proportion of First Nations/Native cigarette butts discarded on post-secondary campuses in the province of Ontario, and potential differences between colleges and universities and across geographical regions.MethodsIn 2009, discarded cigarette butts were collected from high-traffic smoking locations at 12 universities and 13 colleges purposively se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The estimates are computed using a variety of methods to collect data, including collection of empty discarded packs, consumer surveys, seizure data, and other methods. Numerous studies, beginning with Lakhdar (2008), perform discarded-pack studies (Wilson et al, 2009;Merriman, 2010;Barkans and Lawrance, 2013;Davis et al, 2013;Stoklosa and Ross, 2014;Wherry et al, 2014). Many types of surveys can ascertain the prevalence of illicit tobacco purchases, including telephone surveys of areas near Indian reservations (Hyland et al, 2004) and convenience samples of self-identified smokers at bus stops (Wherry et al, 2014).…”
Section: D) Existing or Ongoing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimates are computed using a variety of methods to collect data, including collection of empty discarded packs, consumer surveys, seizure data, and other methods. Numerous studies, beginning with Lakhdar (2008), perform discarded-pack studies (Wilson et al, 2009;Merriman, 2010;Barkans and Lawrance, 2013;Davis et al, 2013;Stoklosa and Ross, 2014;Wherry et al, 2014). Many types of surveys can ascertain the prevalence of illicit tobacco purchases, including telephone surveys of areas near Indian reservations (Hyland et al, 2004) and convenience samples of self-identified smokers at bus stops (Wherry et al, 2014).…”
Section: D) Existing or Ongoing Studiesmentioning
confidence: 99%
“…Large-scale traditional surveys that ask about where cigarettes are purchased include the International Tobacco Control (ITC) Project surveys (Guindon et al, 2014) and the TUS-CPS (Chiou and Muehlegger, 2008;Lovenheim, 2008;DeCicca, Kenkel, and Liu, 2013). Stehr (2005) (Barkans and Lawrance, 2013;Calderoni, 2013;Guindon et al, 2014;Stoklosa and Ross, 2013). And there are few estimates of a change in black-market share in response to a policy change other than a tax increase (Scollo et al, 2014).…”
Section: D) Existing or Ongoing Studiesmentioning
confidence: 99%
“…Evidence of the use of contraband cigarettes is also available from direct cigarette butt collection [ 26 ]. In this method, every butt within a specified area is collected and sorted into legitimate and contraband groups.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the direct collection of cigarette butts can provide an explicit estimate of the proportion of contraband cigarettes being smoked by location. This methodology is unobtrusive and avoids the social desirability bias that may be present in self-reported surveys [ 26 ]. The Canadian Convenience Store Association commissions ad hoc cigarette butt studies and in 2009, suggested that 30 % of cigarette butts collected from 110 sites in Ontario were contraband; however, limited information is available regarding the methodology and sampling used in this study [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation